"A poet is a theologian": wonder and sacrament in the work of Patrick Kavanagh - Corcoran, Paul (My University, 2024)
This study undertakes an in-depth theological exploration of Patrick Kavanagh’s declaration that “a poet is a theologian”. To this end, the thesis assesses Kavanagh’s claim under the two headings of ‘wonder’ and ‘sacrament’, each with their own interdisciplinary relevance to the dual-identity of Kavanagh’s poet-theologian. In the first half of the thesis, wonder emerges as a common starting point for the search for meaning undertaken by both poetry and theology. It is argued that the idea of a ‘Christian’ wonder, rooted in Aquinas’ defining treatment of the virtues, characterizes the child-like innocence at the heart of Kavanagh’s writing. Aquinas, it will be demonstrated, acts as a kind of representative for the theological tradition and a model for the element of balance and authority Kavanagh aims for in the figure of the poet-theologian. In the second half of the thesis, a study of the sacraments of the church underscores the conditions under which the concept of ‘sacramentality’ can act as the means for a rich dialogue between poetry and theology in Kavanagh’s work. Sacramentality locates God’s self-disclosure, as Kavanagh does, in “the bits and pieces of Everyday”. Kavanagh’s approach as poet-theologian, it is argued, is driven by a concerted and considered theological impulse in Kavanagh to rebalance the dour religious landscape of Ireland in his lifetime. Sacramentality, it is demonstrated, holds the key to this mission of the poet-theologian, who travesties the theological environment of his time in order to highlight and correct its shortcomings. In the end, Kavanagh extends his poetry into the realm of theology in order to claim for his work the breadth, the balance, and the authority necessary to present a more imaginative vision of the divine, and to challenge a religious hierarchy who “act as if they’ve kidnapped God, were holding him in a church, and they were the only ones who can understand or talk to him.”
Keywords: Patrick Kavanagh, wonder, sacrament, theologian, poet